Application of the Champion Health Belief Model to determine beliefs and behaviors of Turkish women academicians regarding breast cancer screening: A cross sectional descriptive study - Nukhet Kirag; Mehtap Kızılkaya (BMC, 2019)
Abstract Background Breast cancer is an important cancer type and the most common malignancy among women in both developed and developing countries and the second leading cause of cancer death in women worldwide. This study aimed to examine the projected risk of breast cancer in Turkish women academician, determine the levels of their breast cancer screening behaviors and uncover the relationship between their health beliefs and screening behaviors. Methods This cross-sectional descriptive study was conducted from March to July 2018 in the province of Aydın, Turkey with a total of 200 female academicians. The data were collected using questionnaires filled out by the participants and the Turkish version of the Champion Health Belief Model Scale. Data were analyzed using t test, ANOVA, Chi-square and logistic regression performed with Statistical Package for Social Sciences version 20. Results The mean age of the female academics was 36.1 ± 0.53 years. The female performing breast self-examination had higher perceived sensitivity (OR = 2.88, 95% Cl 1.32, 2.66) benefits to breast self-examination (OR = 0.90, 95% Cl 0.82, 0.99), self-efficacy (OR = 0.87, 95% Cl 0.81, 0.93) health motivation (OR = 1.74, 95% Cl 0.50, 0.90), benefit to mammography (OR = 0.97, 95% Cl 0.88, 1.08), lower barrier to mammography (OR = 1.05, 95% Cl 1.0, 1.09) than women who did not. Female academics with clinical breast examination had higher self-efficacy (OR = 0.91, 95% Cl 0.86, 0.97) and lower barrier to mammography (OR = 1.06, 95% Cl 1.02, 1.10) than women who did not. The female with take mammography had higher sensitivity (OR = 0.84, 95% Cl 0.72, 0.98), lower barrier to breast self-examination (OR = 1.08, 95% Cl 1.02, 1.15) and lower barrier to mammography (OR = 1.09, 95% Cl 1.04, 1.14) than female who did not. Conclusions Female academicians in Turkey exhibit positive attitudes towards breast self-examination, clinical breast examination and mammography as they have higher perceived sensitivity against breast cancer, self-efficacy and fewer barriers. Long-term community-based programs should be extended to different groups of women from a variety of socio-demographic environments.